The Influence of Perceived Green E-Wom on Brand Loyalty: the Mediating Role of Brand Trust - Mardhatilah, Dina; Kifli, Fahmi (Syntax Literate, 2025)
This study aims to examine the effect of perceived green e-WOM on social media on brand loyalty, with brand trust as a mediating variable among coffee consumers in Indonesia. The rising consumer awareness of sustainability has prompted coffee brands to adopt green marketing practices, which in turn influence consumer perceptions formed through e-WOM. Data were collected through an online survey involving 100 respondents from Indonesia's youth who actively interact with e-WOM. The findings show that e-WOM credibility significantly and positively affects brand trust, while e-WOM quality and quantity did not show significant effects. Furthermore, brand trust plays a crucial role in enhancing brand loyalty. This research provides insights into the importance of e-WOM credibility in building brand trust and loyalty, especially in the environmentally friendly product industry.